(untitled) (Journal of the Sylhet Agricultural University, 2026)
An experiment was conducted at the experimental field of the Department of Agronomy and Haor Agriculture, Sylhet Agricultural University, Sylhet, Bangladesh during October 2015 to October 2016 to find out the effect of environmental factors on growth and yield performances of the mungbean varieties in Sylhet region. At the present experiment mungbean variety BARI mung-6 was evaluated at thirteen different sowing dates started from October 2015 (S1) to October 2016 (S13). Due to unfavorable environmental conditions, only plants grown from nine sowing dates could successfully complete vegetative and reproductive phase. The experiments were laid out in a Randomized Complete Block Design (RCBD) with three replications and maintain 3 plots for each sowing time. The combinations of treatments were allocated randomly to the plots in each replication. The unit plot size was 10 m2 (4m × 2.5m). The distance between the replication was 1.0 m and the adjacent unit plot was 0.5 m. The result of the experiment revealed that maximum temperature, minimum temperature, average temperature had positive relationship along with other factors on yield and yield attributes of mungbean. Temperature parameters showed significant positive correlations (p≤0.01) with most growth and yield attributes, while relative humidity and rainfall showed weaker, non-significant associations. The highest grain yield (866.07 kg ha-1) was obtained 1 October, 2015 sowing and lowest (131.79 kg ha-1) was obtained 1 November, 2015 sowing (S2). The results also showed that BARI mung-6 performed better in 1 October, 2015 sowing and 8 April, 2016 sowing in Sylhet. J. Sylhet Agril. Univ. 12(2): 97-104, 2025